(untitled) (Indonesian Tax Justice Review, 2024)
Carbon taxation is increasingly promoted as an instrument to address climate change while mobilizing public revenue. However, its justice implications for developing countries remain underexplored. This paper examines Indonesia’s carbon tax policy through the lens of fiscal and environmental justice. Using normative policy analysis, the study evaluates the alignment of Indonesia’s carbon tax design with equity principles, including the ability-to-pay principle, intergenerational justice, and common but differentiated responsibilities. The analysis shows that while carbon taxation can support emissions reduction, its distributive effects may disproportionately burden lower-income households without adequate compensatory mechanisms. Furthermore, limited international climate finance constrains developing countries’ capacity to implement just carbon pricing. This paper contributes to the global tax justice discourse by highlighting the need to integrate carbon taxation with social protection policies and international support frameworks. Indonesia’s case provides a valuable Global South perspective on balancing environmental responsibility with developmental equity, offering lessons for designing carbon taxes that are both effective and just in emerging economies.